The Mediating Role of Emotion Regulation in Explaining the Causal Relationships Between Childhood Trauma and Pain in Women with Rheumatoid Arthritis - Mardan, Fahimeh; Ghodsi, Parvaneh; Keykhosrovani, Mouloud; Amini, Naser; Leilabadi, Leida (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to investigate the mediating role of emotion regulation in explaining the causal relationships between childhood trauma and pain in women with rheumatoid arthritis. Methods and Materials: In a cross-sectional study based on structural equation modeling, during the period from December 2022 to June 2023, 286 participants diagnosed with rheumatoid arthritis, who had been referred to three hospitals (Loghman, Taleghani, and Shahid Tajrish) in Tehran, were selected using purposive sampling. After obtaining informed consent and meeting the inclusion criteria, they were enrolled in the study. Three indices—childhood trauma, pain, and emotion regulation—were assessed at one time point by the participants. Data were analyzed using SPSS and AMOS software version 25. Findings: Data analysis showed that both emotion regulation strategies, reappraisal (β = 0.068, p = 0.001) and emotional suppression (β = 0.140, p = 0.001), positively and significantly mediated the relationship between childhood trauma and pain in women with rheumatoid arthritis. Conclusion: The findings of this study, consistent with previous research, indicate an association between childhood trauma and pain mediated by emotion regulation. However, in patients with rheumatoid arthritis, pain and other psychological variables exhibit a complex relationship that requires further research.